2018
DOI: 10.1103/physrevapplied.10.064050
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Electrical Spin Conversion in a Biased Ferromagnetic Tunnel Contact

Abstract: The conversion of spin information into electrical signals is indispensable for spintronic technologies. Spin-to-charge conversion in ferromagnetic tunnel contacts is well-described using linear (spin-)transport equations, provided that there is no applied bias, as in nonlocal spin detection. It is shown here that in a biased ferromagnetic tunnel contact, spin detection is strongly nonlinear. As a result, the spin-detection efficiency is not equal to the tunnel spin polarization. In silicon-based 4-terminal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
7
16
1
Order By: Relevance
“…While this reasoning seems to qualitatively capture the trend observed in most experimental results, there still exists some features that remain unexplained [19]. Notably in their explication of the origin of the non-linearity, the fact that the increase of applied voltage needed to compensate the loss of current after spin precession (i. e., the spin voltage) becomes sensitive to the increase of junction bias, leading to a P det independent on the bias.…”
Section: Non-linear Modelmentioning
confidence: 67%
See 3 more Smart Citations
“…While this reasoning seems to qualitatively capture the trend observed in most experimental results, there still exists some features that remain unexplained [19]. Notably in their explication of the origin of the non-linearity, the fact that the increase of applied voltage needed to compensate the loss of current after spin precession (i. e., the spin voltage) becomes sensitive to the increase of junction bias, leading to a P det independent on the bias.…”
Section: Non-linear Modelmentioning
confidence: 67%
“…Although the linear theory for spin injection and detection captures the essential mechanisms of these processes, deviations from the linear model have been systematically reported in experiments based on 3-terminal (3T) Hanle devices and in 4T devices where both injector and detector are under bias [8,12]. Recently, Jansen et al [19] experimentally observed that the spin detection efficiency P det at a tunnel junction strongly depends on the applied bias, offering a way to magnify the detected spin accumulation. In their work, the authors pointed out that the spin signal amplification is inherent to the nonlinear transport occurring at the tunnel junction which arises from the dependence of the transmission probability with the energy of injected carriers.…”
Section: Non-linear Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…2 shows the trend in the reported values of P for Sibased devices. [22][23][24][25][26][27][28][29][30][31] We find that relatively high P values have been reported year by year by using ferromagnet/MgO tunnel barrier contacts. On the other hand, the reported MR ratios measured by local twoterminal measurements were quite small less than 0.01% at room temperature, 15,22,24,30,32) largely inconsistent with the expected values from Eq.…”
Section: Current Status 21 Spin Injection and Detection In Simentioning
confidence: 99%